Pengembangan Media Pembelajaran Matematika Untuk Meningkatkan Kemampuan Komunikasi Matematis Siswa SDN 105343 Ramunia I/II - Anwar, Anwar; Surya, Edi; Fauzi, Kms. Muhammad Amin (Pusdikra Publishing, 2024)
The purpose of this study was to determine: 1) increasing students' mathematical communication skills through the development of developed mathematics learning media. The subjects in this research were 30 class VI students at SDN 105343 Ramunia I/II and the object of this research was to see improvements in the learning process carried out. 2) the effectiveness of media in developing mathematics learning on students' mathematical communication skills. The learning media developed (The media has met the level of validity with a reliability coefficient of 0.790. Based on data obtained from testing the learning media, it is known that: 1) the media developed has been able to meet the effectiveness of the learning process, where: The percentage of student learning completion that reaches the level of ability 86.67% of students' mathematical communication is classical from 30 students, and students' responses to the media and learning process are positive; 2) there was an increase in students' mathematical communication skills using learning media on the subject of blocks, achieving an increase as seen from the percentage of achievement of students' mathematical communication skills in trial I, which was 70.00%, increasing to 86.67% in trial II. With a gain of 0.57 in the medium category.